Wydajność pracy jako element rozwoju gospodarczego - Nyk, Mariusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
For a lot of years the growth of work efficiency has been observed in Polish economy. However, the speed of efficiency change depends on many factors sometimes difficult even to measure. Psychological aspect (employee's mood, way of working etc.) has got great influence on measured value. The approach to the way of work efficiency analysis grows year by year. However, the level of Polish economy's efficiency is half less than the average level in UE. Active membership in UE's structures activates the growth of productiveness. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 329-336